Determinants of early neonatal mortality: secondary analysis of the 2012 and 2017 Indonesia Demographic and Health Survey - Titaley, Christiana Rialine; Mu'asyaroh, Anifatun; Que, Bertha Jean; Tjandrarini, Dwi Hapsari; Ariawan, Iwan (Frontiers in Pediatrics, 2024)
Background: Most neonatal deaths occur during the first week of life (i.e., early neonatal deaths). In this analysis, we aimed to investigate the determinants of early neonatal deaths in a nationally representative sample of births in Indonesia over the five years before each survey.Methods: Data were obtained from the 2012 and 2017 Indonesia Demographic and Health Survey (IDHS), including information from 58,902 mothers of children aged <5 years of age. The outcome variable was early neonatal death (death of a newborn within the first six days of life). Explanatory variables were categorized into environmental, household, maternal, pregnancy, childbirth, and child characteristics. Multivariate regression methods were employed for analysis.Results: Increased odds of early neonatal deaths were associated with mothers who lacked formal education or had incomplete primary schooling (adjusted odd ratio [OR]=2.43, 95% confidence interval [CI]: 1.18-5.01), worked outside the house in agricultural (aOR=5.94, 95% CI: 3.09-11.45) or non-agricultural field (aOR=2.98, 95% CI: 1.88-4.72), and were required to make a joint decision about health care with their partner or another household member (aOR=1.79, 95% CI: 1.12-2.84). Increased odds were also observed in smaller-than-average infants, particularly those who received low-quality antenatal care services (aOR=9.10, 95% CI: 5.04-16.41) and those whose mothers had delivery complications (aOR=1.72, 95% CI: 1.10-2.68) or who were delivered by cesarean section (aOR=1.74, 95% CI: 1.07-2.82). Furthermore, male infants showed higher odds than female infants (aOR=1.85, 95% CI: 1.23-2.76).A multifaceted approach is essential for curtailing early neonatal mortality in Indonesia. Enabling workplace policies, promoting women's empowerment, strengthening the health system, and improving the uptake of high-quality antenatal care services are among the critical steps toward preventing early neonatal deaths in Indonesia.